Financial Literacy and Understanding for Individuals or Small Business Owners in the Framework of Financial Accounting - Ms. Ruhiya Nazneen (Journal of Corporate Finance Management and Banking System, 2024)
This Study Examines Financial Accounting's Development And Impact On Corporate Decisions. We Show The Flow Of Financial Data From Journal Entries To Important Financial Statements, The Profit And Loss Account, And The Balance Sheet Using A Graphic Flowchart. We Examine How Financial Analysis Affects Business Reporting And Choices. The Flowchart Helps Explain Financial Accounting's Complexities. Financial Accounting's Key Steps Are Shown In The Flowchart. We Noticed That Transactions Begin In The Journal. These Entries Are Combined In The Ledger To Show Account Balances Vividly. Revenues And Costs Determine The Net Profit Or Loss In The Profit And Loss Account. A Company's Assets, Liabilities, And Equity Are Shown On The Balance Sheet Immediately. Their Relationship Shows The Balance Between Financial Stability And Profitability. Financial Analysis Is Vital To Decision-Making. Organizations May Assess Their Financial Health And Plan Forward By Reviewing Their P&L And Balance Sheet. This Study Concludes That Financial Accounting And Analysis Are Crucial To Company Choices.